STRUCTURAL ANALYSIS OF NOVEL ASYBÂH AL-JAHÎM WORKS OF YASMINA KHADRA TRANSLATED BY MUHAMMAD SYARI - Iin Suryaningsih (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2021)
Structural is one of approaches in literature that emphasizes the relationship between its elements, whether it is intrinsic or extrinsic. Among the study of the intrinsic elements are themes, characters and characterizations, setting, time setting, social setting, plot, point of view and mandate. Pattern relationships between these elements will form the unity of the story as in the novel Asybah al-Jahīm. The problem in this research is how is the intrinsic element in novel Asybah al-Jahīm, a work by Yasmina Khadra. This research was focused on the structural intrinsic theory of writers and in the book by Burhan Nurgiyantoro, with qualitative descriptive research method using objective approach. The result of this research shows that the main theme of the novel is Humanism in Political War Conflict. The main characters in the novel /Asybah al-Jahīm / are Yasmina Khadra as “I” character, as well as 21 additional characters. The setting of the place used in the novel Asybah al-Jahīm covers Kafr Karam, Baghdad and Beirut as public places in storytelling. The flow process in the novel storytelling used advanced grooves. The story uses first persona point of view.